Model pengelolaan program adiwiyata dalam membangun budaya peduli lingkungan di MIN 1 kota Malang - Rohmatullah, Ifan (Maliki Interdisciplinary Journal, 2026)
This article examines the management model of the Adiwiyata Program at MIN 1 Kota Malang in fostering an environmentally conscious school culture through systematic and sustainable practices. It highlights the stages of implementing the School-Based Environmental Culture Movement (GPBLHS), the involvement of all school stakeholders, and strategic partnerships with external institutions such as the local water company (PDAM), health centers, and waste banks. The findings indicate that program success is strongly supported by structured planning, the integration of environmental values into learning activities, and active student participation as agents of change. The program is further strengthened by external collaborations that provide facilities, education, and technical assistance. However, several challenges remain, including resistance to environmental initiatives, inconsistent behavioral discipline, and limited supporting facilities. This article concludes that the effectiveness of the Adiwiyata Program depends not only on administrative compliance but also on the internalization of ecological culture through continuous collaboration between schools, families, and communities. These insights are expected to serve as a reference for other educational institutions seeking to develop a holistic and effective Adiwiyata management model.